PENGARUH PDRB SEKTOR PERTANIAN, UPAH MINIMUM, DAN NILAI TUKAR PETANI TERHADAP INFLASI BAHAN MAKANAN DI PROVINSI RIAU - Jarda Anggi; Mayes Anthony; Richard Rahmat (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of Agricultural Sector Economic Growth, Minimum Wage, and Farmer's Exchange Rate on Foodstuff Inflation in Riau Province in 2011-2020. This study uses Time Series data related to research variables in Riau Province in 2011-2020 which are sourced from data from the Central Statistics Agency for Riau Province and Bank Indonesia. This research is a quantitative research. The analysis used is multiple regression analysis. With Operational Variables of Foodstuff Inflation (Y) as the dependent variable, the variable of Agricultural Sector Economic Growth (X1), Minimum Wage (X2), and Farmer's Exchange Rate (X3) as independent variables. The results of this study state that (1) Agricultural Sector Economic Growth has a negative and significant effect on Foodstuff Inflation in Riau Province in 2011-2020. (2) Minimum Wage has a positive and significant impact on Foodstuff Inflation in Riau Province in 2011-2020. (3) Farmer's Exchange Rate has a positive and significant effect on Foodstuff Inflation in Riau Province in 2011-2020. (4) Agricultural Sector Economic Growth, Minimum Wage, and Farmer's Exchange Rate simultaneously affect Foodstuff Inflation in Riau Province in 2011-2020. The influence given by the independent variable to the dependent variable is in a strong influence.Keywords: Inflation, Foodstuffs, Agriculture